Semiconductor-to-metal transition in the bulk of WSe2 upon potassium intercalation. (21st March 2017) - Ahmad, Mushtaq; Müller, Eric; Habenicht, Carsten; Schuster, Roman; Knupfer, Martin; Büchner, Bernd
Abstract: We present electron energy-loss spectroscopic measurements of potassium (K) intercalated tungsten diselenide (WSe2 ). After exposure of pristine WSe2 films to potassium, we observe a charge carrier plasmon excitation at about 0.97 eV, which indicates a semiconductor-to-metal transition. Our data reveal the formation of one particular doped K-WSe2 phase. A Kramers–Kronig analysis allows the determination of the dielectric function and the estimation of the composition of K0.6 WSe2 . Momentum dependent measurements reveal a substantial plasmon dispersion to higher energies.